Digital skills of health care professionals in cancer care: A systematic review - Tuominen, Leena (Sage, 2025)
Background: The digital transformation of healthcare enables new ways of working in cancer care directing attention on the digital skills of healthcare professionals. This systematic review aims to identify existing evidence about digital skills among health care professionals in cancer care to identify the needs for future education and research.
Methods: Database searches were conducted in PubMed, CINAHL, Web of Science, Scopus, Cochrane and ERIC to identify studies until March 2023. The inclusion criteria were digital skills of health care professionals in cancer care as described by themselves, other health care professionals, patients or significant others. The CASP tool was used for quality assessment of the studies. Data was analysed following inductive content analysis.
Results: The search produced 4563 records, of which 24 studies were included (12 qualitative, 10 quantitative, 1 mixed methods design and 1 strategy paper). Four main categories were identified describing HCPs' required skills, existing skills and development areas of digital skills in cancer care: Skills for information technology, Skills for ethical practice, Skills for creating a human-oriented relationship and Skills for digital education and support. In development areas, one more main category, Skills for implementing digital health, was identified.
Conclusion: The digital skills of health care professionals in cancer care are multifaceted and fundamental for quality cancer care. The skills need to be assessed to provide education based on actual learning needs. The review findings can be used for education and research in this field.